Archäozoologie des Mittelalters: "Human-Animal Studies" jenseits von Schrift- und Bildquellen - Chaput, Francoise; Mehler, Natascha; Pasda, Kerstin; Paxinos, Ptolemaios; Trixl, Simon (Das Mittelalter, 2023)
Animals were indispensable to all pre-modern societies. In the Middle Ages, livestock contributed significantly to the development of human communities. By reconstructing the human-animal relationship through the ages by means of faunal remains from archaeological sites, archaeozoology sheds light on the role of medieval livestock alongside written and iconographic sources. Our paper illustrates this with four species-specific case studies: cattle, dogs, cats, and fish. As a source of food, labour, and various raw materials, cattle were of fundamental economic importance. Among other things, this can be recognized in the increasing proportion of cattle remains in Central European settlements during the High Middle Ages. At the same time, in urban contexts, masses of bone-carving waste products illustrate the importance of cattle bones for this widespread handicraft. In rural milieus, the use of cattle as draught animals is evident from specific limb pathologies. The role of dogs varied depending on the social context, as evidenced by a comparison of faunal data from castles and towns: individuals from elite contexts reached extreme body sizes and a higher age compared to urban dogs. This leads to the assumption that dogs in medieval castles fulfilled specific functions as well-kept hunting companions and pets. Cut marks also prove the consumption of dog meat during the Middle Ages, at least in exceptional situations. Skin processing, however, was more the rule. This also applies to cats, as bone finds with characteristic cut marks from various high and late medieval contexts demonstrate. In the early Middle Ages, the cat was also part of funerary rites. Lastly, fish played an increasingly important role during the Middle Ages. With monasteries spreading across Europe, systematic carp breeding emerged. Archaeozoological finds from monasteries provide insight into the importance of pond farming and the use of local waters.